Identification and Protective Efficacy of Eimeria tenella Rhoptry Kinase Family Protein 17 - Xiaoxin Liu; Bingjin Mu; Wenbin Zheng; Yijing Meng; Linmei Yu; Wenwei Gao; Xingquan Zhu; Qing Liu (Animals, 2022)
Eimeria tenella encodes a genome of approximately 8000 genes. To date, however, very few data are available regarding E. tenella rhoptry kinase family proteins. In the present study, the gene fragment encoding the mature peptide of the rhoptry kinase family protein 17 of E. tenella (EtROP17) was amplified by PCR and expressed in E. coli. Then, we generated polyclonal antibodies that recognize EtROP17 and investigated the expression of EtROP17 in the merozoite stage of E. tenella by immunofluorescent staining and Western blot analysis. Meanwhile, the protective efficacy of rEtROP17 against E. tenella was evaluated in chickens. Sequencing analysis showed that a single base difference at sequence position 1901 was observed between the SD-01 strain and the Houghton strain. EtROP17 was expressed in the merozoite stage of E. tenella. The results of the animal challenge experiments demonstrated that vaccination with rEtROP17 significantly reduced cecal lesions and oocyst outputs compared with the challenged control group. Our findings indicate that EtROP17 could serve as a potential candidate for developing a new vaccine against E. tenella.